1990
DOI: 10.2105/ajph.80.5.594
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide in indoor ice skating rinks: evaluation of absorption by adult hockey players.

Abstract: We evaluated alveolar carbon monoxide (CO) levels of 122 male, adult hockey players active in recreational leagues of the Quebec City region (Canada), before and after 10 weekly 90-minute games in 10 different rinks. We also determined exposure by quantifying the average CO level in the rink during the games. Other variables documented included age, pulmonary function, aerobic capacity, and smoking status. Environmental concentrations varied from 1.6 to 131.5 parts per million (ppm). We examined the absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Skaters are probably the most susceptible to health effects of air pollutants in an ice skating rink since ventilation rates while skating are expected to exceed normal resting breathing rates by three to five times. 4 The detailed study by Lee and colleagues31 adds insight into the peak nitrogen dioxide concentrations produced inside ice rinks. If the temporal distribution of nitrogen dioxide and carbon monoxide concentrations in ice rinks are similar, we estimate that 1-hour nitrogen dioxide concentrations would be two to five times the measured 1-week average ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Skaters are probably the most susceptible to health effects of air pollutants in an ice skating rink since ventilation rates while skating are expected to exceed normal resting breathing rates by three to five times. 4 The detailed study by Lee and colleagues31 adds insight into the peak nitrogen dioxide concentrations produced inside ice rinks. If the temporal distribution of nitrogen dioxide and carbon monoxide concentrations in ice rinks are similar, we estimate that 1-hour nitrogen dioxide concentrations would be two to five times the measured 1-week average ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…are numerous. Contamination by carbon monoxide ( CO ) ( Anderson, 1971;Miller et al, 1989;Le Âvesque et al, 1990;Kwok, 1993;Lee et al, 1993;Johnson et al, 1995 ) is discussed in particular, but also nitrogen dioxide (NO 2 ) (Hedberg et al, 1989;Lee et al, 1993 ). Almost invariably, the source of the problem was the improper adjustment of the resurfacing machine combined with inadequate building ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have indicated that high concentrations of carbon monoxide (CO) in ice rinks can result in toxicity. [1][2][3][4][5][6] More recently, acute respiratory illness due to nitrogen dioxide (NO 2 ) exposure has also been reported at indoor ice rinks. [7][8][9][10] Acute exposure (for 1 hour or less) to NO 2 concentrations above 5-10 parts per million (ppm) may produce severe cough, hemoptysis, chest pain, and pulmonary edema.…”
Section: Introductionmentioning
confidence: 99%